Clinical manifestations, courses, and outcomes of systemic lupus erythematosus in the dwellers of Kyrgyzstan - G. M. Koilubaeva (Научно-практическая ревматология, 2016)
Objective: to investigate the clinical manifestations, courses, outcomes, and unfourable predictors of systemic lupus erythematosus (SLE) in the dwellers of Kyrgyzstan.Subjects and methods. The investigators carried out a retrospective analysis of 107 patients with SLE, who fulfilled the respective 1982 American College of Rheumatology (ACR) criteria and had been examined and treated at the Clinic of the National Center for Cardiology and Therapy in 2001 to 2011, and a prospective follow-up of 75 of them until 2015. During the prospective follow-up study, 29 of the 75 patients died on average of 6.38±3.48 years after the first visit to the clinic and 46 were alive at the completion of the investigation. The patients’ baseline status was retrospectively analyzed. Disease activity was assessed using SLEDAI-2K. The outcome of SLE was determined as the number of exacerbations by the SLE flare index (SFI): moderate or severe, the occurrence of a complete or drug-induced remission, the development of irreversible organ damages by the Systemic Lupus International Collaborating Clinics/ACR damage index (SLICC/ACR DI) or death.Results and discussion. The prospective follow-up study showed that among the 75 patients, only one achieved a complete clinical and immunological remission and 12 had drug-induced remission. All patients with significantly lower disease activity were observed to have a statistically significant DI increase by one or more scores (p < 0.05). Various irreversible organ damages were detected in 48 (64%) patients; these were found in the survivors 3.5 [2.0; 5.0] years after their first visit and in the deceased patients 1.5 [1.0; 3.0] years prior to death. The main causes of death were renal and pulmonary complications in 10 (34.5%) and 7 (24.1%) patients, respectively. Respiratory infections as severe pneumonias with progressive respiratory failure result in a fatal outcome in 5 (17.2%) cases. The independent risk factors for death were acute course (β = 0.18; p = 0.04), long disease duration out of remission (β = 0.51; p = 0.001), and SLICC/ACR DI progression (β = 0.32; p = 0.0004). High SLE activity failed to affect mortality rates (β = 0.09; p = 0.02) that showed no significant decrease over time (p = 0.14).Conclusion. The poor predictors in patients with SLE were acute course, long disease duration out of remission, and progression of irreversible organ damages.